The use of a Swedish telephone medical advice service by the elderly - a population-based study - K. Dahlgren; M. J. Holzmann; A. C. Carlsson; P. Wändell; J. Hasselström; T. Ruge (Taylor & Francis Group, 2017)
Objective: The present study aimed to describe contact made by the elderly to Sweden's nationwide medical helpline, Healthcare Guide 1177 by Phone (HGP). Other objectives were to study potential gender differences and the association between different HGP referral levels and acute visits to hospital-based emergency departments and acute visits to primary care centres. Design: De-identified data from recorded calls to HGP was extracted for analysis (n = 7477 for the oldest age group). Information about acute visits to emergency departments and to primary care reception was extracted from the patient administration system. Setting: Västerbotten County, Sweden. Subjects: Patients over 80 years. Main outcome measures: Calling and visiting frequencies for different age groups as well as reasons for contact and individual recommendations. Results: The utilisation rate of the telephone advice service for the oldest age group was high, with an incidence rate of 533 per 1000 person-years. Women had a 1.17 times higher incidence rate compared with men. The most common reason for contact was drug-related questions (17% of all contacts). Calls that were recommended to care by a medical specialist correlated with total emergency department visits (r = 0.30, p < 0.05) and calls that were given advice correlated with acute primary healthcare visits (r = 0.38, p = 0.005). Conclusion: The high utilisation of the telephone advice service by the elderly gives the telephone advice service a unique ability to function as a gatekeeper to further healthcare. Our data suggest that with the telephone advice service's present guidelines, a significant proportion of all calls are being directed to further medical help. The high frequency of drug-related questions raises concerns about the elderly's medication regimens.Key points Patients over 80 years of age had a high utilisation of the telephone medical advice service compared with other age groups. Drug-related questions were the most common reason for contact. A significant proportion of all calls made resulted in further heatlhcare contacts.